GOVERNMENT AFFAIRS WEEKLY REPORT (Tufts Archival Research Center, 2007)
Weekly report of government affairs. Lists different issues, such as cigarette taxes, smoking restrictions, smoking related legislation among others, and gives information by state in each catergory.